Penyelesaian Pelanggaran Hak Asasi Manusia Yang Berat Masa Lalu Melalui Mekanisne Non-Yudisial (Studi Terhadap Keputusan Presiden Nomor 17 Tahun 2o22 Tentang Pembentukan Tim Penyelesaian Non Yudisial Pelanggaran Hak Asasi Manusia yang Berat Masa Lalu) - Yunita Syofyan; Didi Nazmi (UNES Law Review, 2023)
Based on Law No.26 of 2000 TentaofHuman Rights Court, apart from going through court, past serious human rights violations can be resolved through non-judicial mechanisms. Formation of a non-judicial resolution team for past serious human rights violations based on Presidential Decree Number 17 of 2022 whose task is to carry out non-judicial tasks to reveal cases of serious human rights violations and recommend concrete and dignified remedies for victims of serious human rights violations. Then. The question is, does the Non-Judicial Resolution Team for Past Serious Human Rights Violations have non-judicial authority in disclosing cases of past gross human rights violations?